PENINGKATAN MINAT BACA MASYARAKAT MELALUI PEMBANGUNAN PERPUSDES SEBAGAI OBJEK WISATA EDUKASI BERBASIS KEARIFAN LOKAL DI DESA MAPPER, KABUPATEN PAMEKASAN - Darwis; Campina Illa Prihantini; FARIDATUL MUSFIROH (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2020)
PERPUSDes Mapper Village is the only village library in Pamekasan Regency. This library is managed by village youths who have enthusiasm in efforts to increase reading interest in the Pamekasan Regency community in general and the Mepper Village community in particular. Over time, PERPUSDes Mapper Village began to be known by the wider community, but library management has not been optimal. Community service activities were initiated by STIE Bakti Bangsa students through the Village Development Holistic Program with the aim of increasing public interest in reading. Several activities and empowerment programs for the Mapper Village PERPUSDes manager were provided so that the library could develop and could help increase public interest in reading. The results of this community service show that with the availability of reading media, such as the increasing number of reading books, a set of computers, the improvement of reading rooms, and the procurement of spot selfies at several points around the library, has been proven to increase the number of visits at the Mapper Village PERPUSDes.